The Effect of Competence, Discipline, and Work Motivation on Job Satisfaction and Affective Commitment of School Administration Staff (TAS) at SMA Se Sunggal District, Deli Serdang Regency - Nurhamida; yohny anwar (Yayasan Multidimensi Kreatif, 2024)
The research aims to analyze the effects of: (1) competence on job satisfaction; (2) discipline towards job satisfaction; (3) work motivation on job satisfaction; (4) competence towards affective commitment; (5) discipline towards affective commitment; (6) work motivation towards affective commitment; (7) job satisfaction with affective commitment; (8) job satisfaction in moderating competence towards affective commitment; (9) job satisfaction in moderating discipline towards affective commitment; and (10) job satisfaction in moderating work motivation towards affective commitment to School Administration Personnel in High Schools in Sunggal District. The research population is School Administration Personnel in high schools in Sunggal District with a sample of 136 people. The research method is a quantitative method with Smart-PLS analysis. The results of the study concluded: (1) the influence of competency variables on job satisfaction was 27.1%; (2) the influence of the discipline variable on job satisfaction was 26.5%; (3) the magnitude of the influence of the work motivation variable on job satisfaction was 34.8%; (4) the influence of competency variables on affective commitment is 12.5%; (5) the influence of the discipline variable on affective commitment was 71.4%; (6) the influence of work motivation variables on affective commitment is 26.5%; (7) the magnitude of the influence of the job satisfaction variable on affective commitment was 16.6%; (8) the influence of the competency variable on affective commitment with job satisfaction moderation was 11.8%; (9) the influence of the discipline variable on affective commitment with job satisfaction moderation was 11.7%; and (10) the influence of the work motivation variable on affective commitment with job satisfaction moderation was 12.3%. Overall, the results of the study showed that affective commitment was influenced by competence, discipline, and work motivation on job satisfaction by 74.0%; While the remaining 26.0% is determined by other factors.